Incidence and time course of everolimus-related adverse events in postmenopausal women with hormone receptor-positive advanced breast cancer: insights from BOLERO-2 - Hope S. Rugo; Kathleen I. Pritchard; Michael Gnant; Shinzaburo Noguchi; Martine Piccart; G. N. Hortobagyi; José Baselga; Alejandra Perez; Matthias Geberth; Tibor Csőszi; E. Chouinard; Vichien Srimuninnimit; et al. (2014)
In the BOLERO-2 trial, everolimus (EVE), an inhibitor of mammalian target of rapamycin, demonstrated significant clinical benefit with an acceptable safety profile when administered with exemestane (EXE) in postmenopausal women with hormone receptor-positive (HR(+)) advanced breast cancer. We report on the incidence, time course, severity, and resolution of treatment-emergent adverse events (AEs) as well as incidence of dose modifications during the extended follow-up of this study.